2013
DOI: 10.4049/jimmunol.1300522
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Disease during Streptococcus pneumoniae Acute Lung Infection Requires 12-Lipoxygenase–Dependent Inflammation

Abstract: Acute pulmonary infection by Streptococcus pneumoniae is characterized by high bacterial numbers in the lung, a robust alveolar influx of polymorphonuclear cells (PMNs) and a risk of systemic spread of the bacterium. We investigated host-mediators of S. pneumoniae-induced PMN migration and the role of inflammation in septicemia following pneumococcal lung infection. Hepoxilin A3 (HXA3) is a PMN chemoattractant and a metabolite of the 12-lipoxygenase (12-LOX) pathway. We observed that S. pneumoniae infection in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
140
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 78 publications
(149 citation statements)
references
References 56 publications
9
140
0
Order By: Relevance
“…Robust recruitment of PMNs into alveolar spaces is a hallmark of pneumococcal pneumonia, and we previously showed that blocking the 12-LOX pathway abrogated PMN migration response across pulmonary epithelia (27). As arachidonic acid (AA) is the substrate for 12-LOX activity, we sought to determine whether pneumococcal infection leads to AA release from pulmonary epithelial cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Robust recruitment of PMNs into alveolar spaces is a hallmark of pneumococcal pneumonia, and we previously showed that blocking the 12-LOX pathway abrogated PMN migration response across pulmonary epithelia (27). As arachidonic acid (AA) is the substrate for 12-LOX activity, we sought to determine whether pneumococcal infection leads to AA release from pulmonary epithelial cells.…”
Section: Resultsmentioning
confidence: 99%
“…Infection with B. subtilis resulted in significantly less release of AA than with the S. pneumoniae strains (2.5-fold lower than with strain TIGR4 and 2-fold lower than with strains D39 and G54; at 5 h postinfection, P Ͻ 0.005, P Ͻ 0.05, P Ͻ 0.05, respectively) and was statistically indistinguishable from treatment with HBSS. Strain TIGR4 (55) was previously used for monolayer and murine infection experiments (27,56), including in investigations that revealed 12-LOX-dependent inflammation, and thus was utilized for the studies described below. cPLA 2 has a high specificity for membrane phospholipids with AA at the sn-2 position, and its activation has been implicated in AA release and inflammation (54,57).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated that pathogen-infected epithelial layers facilitate neutrophil trans-epithelial migration 3,8,19,[24][25][26][27][28]31,32 . This occurs via a pathogen-specific induction of an epithelial cell-derived neutrophil chemotactic gradient 3,23 .…”
Section: Representative Resultsmentioning
confidence: 99%
“…Furthermore, several additional strains of P. aeruginosa including clinical isolates from cystic fibrosis patients have been validated as inducers in this assay 25 . Streptococcus pneumoniae and Klebsiella pneumoniae, Gram-positive and Gram-negative bacterial pathogens, respectively, are commonly associated with pneumonia and have been shown to be capable of inducing neutrophil trans-epithelial migration using the in vitro coculture model 26,32 . Thus, this model system offers a robust in vitro approach using human derived cells to explore inflammatory processes instigated by mucosal pathogens.…”
Section: Representative Resultsmentioning
confidence: 99%